Bible and cinema: an introduction - Reinhartz, Adele (Routledge, 2013)
"This is a comprehensive introduction to the ways in which the Bible has been used and represented in mainstream cinema. Adele Reinhartz considers the pervasive use of the Bible in feature films, and the medium of film as part of the Bible's reception history. The book examines how films draw on the Old and New Testament and the figure of Jesus Christ in various direct and indirect ways to develop their plots, characters, and themes. As well as movies that set out explicitly to retell biblical stories in their ancient context, it explores the ways in which contemporary, fictional feature films make use of biblical narrative. Topics covered include:how filmmakers make use of scripture to address and reflect their own time and place.the Bible as a vehicle through which films can address social and political issues, reflect human experiences and emotions, explore existential issues such as evil and death, and express themes such as destruction and redemption.the role of the Bible as a source of ethics and morality, and how this connection is both perpetuated and undermined in a range of contemporary Hollywood films. films that create an experience of transcendence, and the ways in which the Bible figures in that experience.Reinhartz offers insightful analysis of numerous films including The Ten Commandments and The Shawshank Redemption, paying attention to visual and aural elements as well as plot, character, and dialogue. Students will find this an invaluable guide to a growing field"--